The Relationship Between Care Givers and The Quality of Life of Older Adults - Wulan Oktaviani Khoirunisa; Dewi Puspitasari; Ummi Malikal Balqis (STIKES Hesti Wira Sriwijaya, 2025)
Introduction: A decrease in the body's ability to deal with stress and physiological conditions is a sign of old age, which is a process that a person has gone through throughout his life. Older residents can improve their quality of life, become more motivated, and live their lives in the role of a good caregiver. Method: The aim of this research is to find out how the role of caregivers affects the quality of life of older people. This research utilizes literature observations and Google Scholar data. Results: There are seven journals that discuss the relationship between health care nurses and the quality of life of older people. Conclusion: There is a correlation between caregiver support and the quality of life of parents.